AGE FALSIFICATION AND ITS IMPLICATION ON AN INDIVIDUAL’S PRODUCTIVITY IN AN ORGANISATION - A. ACHU, AYUK,; EGBE EBAGU, TANGBAN; T. A., OMANG,; FRANCIS, UYANG,; CLETUS EKOK, OMONO; NSOR O, JOHN (International Journal of Psychosocial Rehabilitation, 2021)
The study investigated the impact of age falsification on an individual’s performance in anorganisation. Issues of why the phenomenon continues unabated in Nigeria were discussedand chief among them include: unemployment, poverty and government insensitivity to itscitizens as concern prompt and regular payment of their retirement benefits. The study madesome recommendations which include: Nigerian government should re-evaluate her policy ofemployment that excludes energetic young persons who are willing to work, on account ofage (you must not be above 30 years); Government should objectively and without delay payoff the entitlement of all retirees as this would hitherto allay the fears of Nigerians fromretiring as of when due; and, Government through its relevant agencies should arrest andprosecute the perpetrators and accomplices that aid and abet age forgery.